Biomedical instrumentation : technology and applications - Khandpur, Raghbir Singh (New York Mcgraw-Hill, 2005)
One of the most comprehensive books in the field, Biomedical Instrumentation rigorously covers the latest developments in medical imaging systems, gamma camera, PET camera, SPECT camera and lithotripsy technology.
Keywords: Biomedicina; Instrumentacion Biomedica; Monitoreo; Funcion Pulmonar